2019
DOI: 10.3390/su11010243
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Sustainable Room for Growth for a Particular Romanian Tourism Area of Business: The Case of Accommodation Businesses

Abstract: In recent years, the Romanian accommodation business sector has recorded a dramatic increase in accommodation units, but even under these circumstances it is below half of the average registered by the European Union. The study aims to evaluate whether there is still room for sustainable growth in this regard. For this purpose, the accounting–financial indicators have been assessed for an annual average of 3447 companies reporting every year to the European Union for 18 years, between 1999 and 2016, for all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Based on the results (2), the initial approach was to calculate the annual number of overnight stays' estimation based on RUZ (n_acc_ruz) and RPO (n_acc_rpo) data on the number of accommodation service providers (6). Afterwards, the estimated number of taxable nights based on RUZ (n_nights_ruz) and RPO (n_nights_rpo) data and the ratio of taxable nights (ratio_taxable_nights) calculation was planned (7).…”
Section: Ratio Of Taxable Overnight Stays (Ratio_taxable_nights) = Numentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results (2), the initial approach was to calculate the annual number of overnight stays' estimation based on RUZ (n_acc_ruz) and RPO (n_acc_rpo) data on the number of accommodation service providers (6). Afterwards, the estimated number of taxable nights based on RUZ (n_nights_ruz) and RPO (n_nights_rpo) data and the ratio of taxable nights (ratio_taxable_nights) calculation was planned (7).…”
Section: Ratio Of Taxable Overnight Stays (Ratio_taxable_nights) = Numentioning
confidence: 99%
“…Estimated number of theoretical number of overnight stays (n_nights_ruz_rpo_susr_tax) = Number ASPs based on the mean of input data (avg_acc_ruz_rpo_susr_tax) × Average number of overnights per ASP for SUSR (avg_night_per_acc_susr) (10) The final estimation of number of overnight stays (n_nigths_est) was calculated (11) as the average of overnights stays extracted from SUSR (Table 2), and the calculated overnight stays from levied occupancy tax (2), RUZ (6), RPO (6), and theoretical number of overnight stays (10). The last step was to determine the number of taxable nights from the final estimated overnight stays as was planned for RUZ and RPO (6), respectively, to calculate the estimated potential occupancy tax revenues (7).…”
Section: Ratio Of Taxable Overnight Stays (Ratio_taxable_nights) = Numentioning
confidence: 99%
See 1 more Smart Citation
“…ISSN 2345-0282 (online) http://jssidoi.org/jesi/ 2023 Volume 10 Number 3 (March) http://doi.org/10. 9770/jesi.2023.10.3(12) managerial decisions should be made to increase sales, profitability and added value (Berinde & Corpădean, 2019). Research on employees' and guests' sustainable business attitudes and practices demonstrated that employees and guests experienced a great extent of sustainable business attitudes and highly practised sustainability.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Some studies analyzed general factors that affect tourism competitiveness [26][27][28][29], while others assessed the effect of specific factors such as the evolution of tourist inflows [30]; globalization [31]; tourism's contribution to economic growth [32]; corruption [33]; air transportation [34]; the competitiveness of international hotel firms [35]; regional systems of innovation [36] or sustainability, which is the focus of our work [37][38][39][40][41][42][43][44].…”
Section: Literature Reviewmentioning
confidence: 99%